2012
DOI: 10.1155/2012/270404
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Learning in Schools under Sanction

Abstract: The focus on “school turnaround” has become central to policy and practice in the United States as a result of school accountability, yet little remains known about school improvement under sanction. This study uses theories of organizational learning to understand the processes through which educators search for and adopt reform strategies, as well as the extent to which these schools’ organizational culture and climate are conducive to this type of learning. Our mixed methods study involves document analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…[55][56][57] This review identified some studies where the re-use of ideas was not carried out by taking into consideration the local context. 35 Our findings are also supported by the knowledge mobilisation literature, which suggests that whilst ideas for improvement may easily spread across boundaries, they might not achieve local buy-in and a good 'epistemic fit' within local contexts, especially if there is a lack of knowledge brokering and senior support to encourage organisations to be receptive to the new ideas. 58 The findings in relation to the implementation of successful interventions mirrors other analyses of improvement interventions, where success is often associated with staff engagement, protected staff time for implementation, clear priority-setting and the use of routine data to monitor progress at Board level.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…[55][56][57] This review identified some studies where the re-use of ideas was not carried out by taking into consideration the local context. 35 Our findings are also supported by the knowledge mobilisation literature, which suggests that whilst ideas for improvement may easily spread across boundaries, they might not achieve local buy-in and a good 'epistemic fit' within local contexts, especially if there is a lack of knowledge brokering and senior support to encourage organisations to be receptive to the new ideas. 58 The findings in relation to the implementation of successful interventions mirrors other analyses of improvement interventions, where success is often associated with staff engagement, protected staff time for implementation, clear priority-setting and the use of routine data to monitor progress at Board level.…”
Section: Discussionsupporting
confidence: 71%
“…External pressures were also seen as negative as in some cases, they resulted in the “repackaging” or “recycling” of ideas and approaches (in the case of this study, restructuring plans) that did not support the meeting of organisational goals or contribute to learning. 35 The external vs. internal debate was also present in studies focusing on school inspections and special measures, where some authors argued in favour of the use of school self-evaluations rather than external inspections. 49 Recent research on the use of inspections in healthcare has also shown no effects in performance generated by external inspections.…”
Section: Resultsmentioning
confidence: 99%
“…Bogler and Somech (2005) state that citizenship behavior exhibited by teachers to students is also a sort of behavior assisting schools to become effective. Similarly, previous studies show that OCB has important effects on organizational performance (Podsakoff and MacKenzie, 1997;Podsakof et al, 2000) and school effectiveness (Özdevecioğlu, 2003;Martinez, 2012;Finnigan, Daly & Stewart, 2012).…”
Section: Discussionmentioning
confidence: 55%
“…As discussed above, cycles of inquiry occupy a central curriculum/content strand within our program. Drawing from the work of one of our colleagues (Smylie, 2010) as well as the work of others (Finnigan & Daly, 2012; Finnigan, Daly, & Stewart, 2012; Robinson, Lloyd, & Rowe, 2008), we have come to view cycles of inquiry as a primary mechanism for cultivating the kinds of organizational learning necessary to promote school-wide improvement. Moreover, cycles of inquiry are critical supports for the work of goal setting and planning for goal achievement (Cosner & Jones, in press), a domain of school leader work that has been found to have a moderate to strong effect on student achievement (Robinson et al, 2008).…”
Section: : Key Program Features Following Redesignmentioning
confidence: 99%
“…That is, our evaluation data can suggest that we have room for program improvement, but these data are not helpful in telling us precisely what to improve. For these reasons and drawing extensively from the literature on more robust data-use practices (Cosner, 2011, 2012, 2014a, 2014b; Finnigan & Daly, 2012; Finnigan et al, 2012; Gallimore, Ermeling, Saunders, & Goldenberg, 2009; Timperley, 2009), we have collected a variety of additional data sources to help us identify program and instructional problems that are likely contributing to or explaining our current outcome data and results. Completing audits of our curriculum in relation to the competencies that our students must develop, reviewing students’ course evaluations, holding student focus groups and administering student surveys that investigate students’ program experiences and self-reported learning outcomes, and examining student course and field work and assessments to locate patterns of problems that we can consider in relation to our curriculum, coaching and instructional practices are additional streams of data that have been particularly instructive for ongoing program improvement.…”
Section: : Key Program Features Following Redesignmentioning
confidence: 99%